Analysis of Cyberbullying Among Students: a Legal Perspective in Indonesia - Herlambang, Dian; Zildjianda, Raesitha; Brajannoto, Destoprani (IAIN Madura, 2025)
Cyberbullying has become a global phenomenon that occurs not only in Indonesia but also in various other countries, so it is a common concern to find solutions to overcome it, mainly because the majority of victims are children. Unfortunately, there are still many countries in the world that do not have specific policies or regulations to deal with cyberbullying. Therefore, preventive measures need to be designed immediately so that children do not become more victims of advances in information technology. This study uses a normative legal research method. The problem that is formulated is how cyberbullying occurs among students in Indonesia and how it is viewed from a legal point of view in Indonesia. According to research conducted by the Center of Digital Society in 2021, 45.35% of 3,077 junior high and high school students were victims of cyberbullying, while 38.41% were perpetrators. In addition, according to UNICEF data from 2022, 45.35% of 2,777 Indonesian students reported having experienced cyberbullying. Despite this, research conducted over the past few years in two European countries indicates that Romania has the highest rate of cyberbullying among remaja, at 37.3%. Other countries in the background are Poland (21.5%) and Greece (28%). Cyberbullying is illegal in Indonesia under Law No. 11 of 2008 about Information and Electronic Transactions (UU ITE). Provisions regarding insults and defamation were regulated in Article 310 of the Criminal Code, paragraphs (1) and (2), but according to Constitutional Court Decision No. 50/PUU-VI/2008, in 2016, Law No. 19 of 2016, an amendment to Law No. 11 of 2008, cyberbullying is legally prohibited.